Detoxification of Oral Exposure to Benzo(a)pyrene by Lactobacillus plantarum CICC 23121 in Mice. Issue 12 (10th May 2021) - Liu, Jinxia; He, Huan; Xu, Mengfan; Wang, Tao; Dziugan, Piotr; Zhao, Hongfei; Zhang, Bolin
Abstract: This study's previous work showed that the carcinogen and mutagen benzo(a)pyrene (BaP) can be adsorbed by Lactobacillus cells in vitro. However, in vivo BaP detoxification by lactic acid bacteria has not yet been investigated. The present study evaluates the effects of orally administered Lactobacillus plantarum CICC 23121 in BaP‐treated mice. Oral administration of 50 mg kg −1 BaP perturbed the intestinal microflora, caused Proteobacteria to predominate, and severely damaged DNA. However, oral administration of 5 × 10 10 CFU mL −1 CICC 23121 in BaP‐treated mice enhances fecal BaP excretion from 181.70 ± 1.04 µg/(g∙h) to 271.47 ± 11.71 µg/(g∙h) after 6 h. Fecal BaP excretion reaches up to 280.66 ± 22.97 µg/(g∙h) after the first 4 days of orally administered CICC 23121 and decreased to 94.31 ± 2.64 µg/(g∙h) by day 11. Intestinal microbiota are restored and Firmicutes predominates. CICC 23121 alleviates BaP‐induced DNA damage and reduces tail length from 56.37 ± 5.31 to 39.69 ± 4.27 µm. Therefore, oral CICC23121 consumption is a promising strategy for reducing BaP toxicity in mice. To the best of our knowledge, this report is the first report to demonstrate in vivo that Lactobacillus cells can detoxify BaP. Abstract : The involvement of strain CICC 23121, by an orally consumed dosage of 5 × 10 10 CFU/mL to BaP‐treated mice, significantly enhances the fecal excretion of BaP from 181.70 ± 1.04 to 271.47 ± 11.71 µg/(g∙h) after 6 h treatment.